Critical factors impacting sustainability of continuous improvement in manufacturing industries in Malaysia - Ali, Aness Janee; Islam, Md. Aminul; Lim, Poon Howe (2009)
The purpose of this research was to investigate the influence of six variables namely strategic focus, monitoring continuous improvement, management of continuous improvement, involvement/engagement, and learning and knowledge sharing on sustainability of continuous improvement capabilities in the context of manufacturing industries in Penang, Malaysia. Data from the email survey on the variables introduced supported that strategic that strategic focus, management of continuous improvement and learning/knowledge sharing has positive influences on sustainability of continuous improvement capabilities in an organization.The implications of this study highlighted that the most effective predictor for sustaining continuous improvement capabilities among manufacturing industries in Penang was strategic focus.